Increasing survival time decreases the cost-effectiveness of using "test & treat to eliminate HIV epidemics - Bradley G. Wagner; Brian J. Coburn; Sally Blower (Mathematical Biosciences and Engineering)
Treating HIV-infected individuals reduces their viral load, consequently increasing their survival time and decreasing their infectivity.It has been proposed that universal testing and treatment (i.e., universal ``test & treat'') could lead to HIV elimination and would be extremely cost-effective.It is now being debated whether to use a universal ``test and treat'' approach in the ``real-world'' as a prevention strategy to control HIV epidemics.However current modeling predictions of the impact, and cost-effectiveness, of universal ``test & treat'' strategies are based on an unrealistically short survival time for treated individuals.Here we use mathematical modeling and a longer, more realistic, survival time.We model the potential impact of a universal ``test & treat'' strategy in South Africa.Our results show that increasing the length of the survival time on treatment, although beneficial to individuals, reduces the probability of eliminating HIV and decreases the cost-effectiveness of using universal ``test & treat'' strategies.Therefore our results show that individual-level benefits and public health benefits will conflict when using ``test & treat'' strategies to reduce HIV transmission.